Reflections on Loyalty as an Ethical and Economic Value - Waszczak, Stanisław (Edukacja Ekonomistów i Menedżerów, 2012)
The article includes reflections on the concept of loyalty, its nature and status as a virtue. The issue of loyalty was shown from different points of view, paying attention to its ethical and economic value, but also the problematic nature, resulting from its internal characteristics and external determinants.